STATUS HAK KEBENDAAN TERHADAP TENCENT SELAKU PEMEGANG HAK MILIK KEBEBASAN YANG MUTLAK ATAS GAME PUBG MOBILE DALAM HUKUM PERDATA - Niken Widya Intan Permatasari; H.R. Adianto Mardijono (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
All human activities and actions always involve objects, and the objects themselves always develop in harmony with the evolution of the times that have developed from the human era. The rules for managing Indonesian objects themselves are regulated in the Civil Code (KUHPerdata) Volume 2. Something is understood to mean anything that can be claimed or owned (Article 499 BW). Entering the era of globalization, information technology plays an important role in changing the pattern of people's lives in various fields, and what is dreamed of is valuable property or possessions. Value here means that it has economic value and can be exchanged for real money through buying and selling transactions or exchange agreements between virtual objects. The dream of virtual property only exists in a virtual world, namely the online world or what is commonly called cyber The purpose of this research is to find out and understand how good legal protection is from Tencent as the absolute owner of virtual property in the PUBG MOBILE game and legal protection for consumers. This research uses a normative juridical method with a statutory and conceptual approach